cGAS-STING Signaling Pathway and Liver Disease: From Basic Research to Clinical Practice - Chen, Bangjie; Rao, Xianyue; Wang, Xinyi; Luo, Zhipan; Wang, Jianpeng; Sheng, Shuyan; Liu, Yuchen; Zhang, Ning; Jin, Shiyu; Chen, Haosong; Sun, Chenyu; Xu, Tao; et al. (Frontiers in Pharmacology, 2021)
The cGAS-STING signaling pathway is an autoimmune inflammatory pathway that can trigger the expression of a series of inflammatory factors represented by type 1 interferon. Recent studies have found that the cGAS-STING signaling pathway played a significant role in liver physiology and was closely related to the progress of liver diseases. For example, activating the cGAS-STING signaling pathway could significantly inhibit hepatitis B virus (HBV) replication in vivo. Moreover, the cGAS-STING signaling pathway was also closely associated with tumor immunity in hepatocellular carcinoma (HCC). This review summarized the role of the cGAS-STING signaling pathway in several common liver diseases, especially the current application of the cGAS-STING signaling pathway in liver disease treatment, and prospected its future research, which provided a new idea for understanding and treating liver diseases.